Exploiting the 1, 2, 3‐Triazole Moiety to Generate Carbazole Molecular Architectures through Click Approach. (29th October 2014) - Ameen, Mohamed A.; El‐Shaieb, Kamal M.; Mohamed, Asmaa H.; Abdel‐Latif, Fathy F.
Abstract : Abstract : Reaction of 3, 6‐dichlorocarbazole with propargyl bromide in the presence of a basic medium gave an N ‐propargylated carbazole. The latter compound was converted into molecular architectures containing 1, 2, 3‐triazole moiety through Cu(I)‐catalyzed1, 3‐cycloaddition reaction with different azides. Similarly, 2‐azidomethyl benzothiazole was cliched with N ‐Boc‐protected N ´‐propargyl glutamate to give the biomolecule 2‐triazolylmethyl product.